(untitled) (Historia, 2021)
Perspective on controversial issues regarding the Great Trek. The Great Trek has come to mean different things to different people. To many Afrikaners it is a heroic phase of their nation’s history and a symbol of freedom, while to Blacks it is a symbol of subjugation and humiliation. Several such controversial issues are discussed here by referring to aspects of the life of the leading Voortrekker figure Sarel Cilliers. The following questions are addressed: Why did the Voortrekkers emigrate? Who was the military commander at the battle of Vegkop? What were the events surrounding the covenant before the battle of Blood River, and, specifically, what role did Sarel Cilliers play in this connection? And lastly: Did the Voortrekkers playa ""civilising"" and ""Christianising"" role in the interior? The author comes to the conclusion that the Voortrekkers were by no means as ""religious"" as they have often been made out to be.